2008
DOI: 10.1007/s10038-008-0283-1
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the FTO gene are associated with severe obesity in the Japanese

Abstract: Variations in the fat-mass and obesity-associated gene (FTO) are associated with the obesity phenotype in many Caucasian populations. This association with the obesity phenotype is not clear in the Japanese. To investigate the relationship between the FTO gene and obesity in the Japanese, we genotyped single nucleotide polymorphisms (SNPs) in the FTO genes from severely obese subjects [n = 927, body mass index (BMI) C 30 kg/m 2 ] and normalweight control subjects (n = 1,527, BMI \ 25 kg/m 2 ).A case-control as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
175
2
10

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 219 publications
(200 citation statements)
references
References 30 publications
13
175
2
10
Order By: Relevance
“…7,8 We found that the SNPs in FTO were significantly associated with BMI, as we have previously reported. 13 We also found that these SNPs were associated with VFA and SFA; however, the association between these SNPs and VFA was marginal because VFA was not significantly different among the genotypes in men. We did not find any association between other SNPs and BMI, VFA or SFA.…”
Section: Discussionmentioning
confidence: 48%
“…7,8 We found that the SNPs in FTO were significantly associated with BMI, as we have previously reported. 13 We also found that these SNPs were associated with VFA and SFA; however, the association between these SNPs and VFA was marginal because VFA was not significantly different among the genotypes in men. We did not find any association between other SNPs and BMI, VFA or SFA.…”
Section: Discussionmentioning
confidence: 48%
“…A cluster of variants in the first intron of FTO show strong and highly significant association with obesity and obesity-related traits in three independent genome-wide association studies, [3][4][5] findings that have been replicated in several other studies. [15][16][17][18] In the present study, we identified three novel SNPs in the fourth intron, which are not in linkage disequilibrium with SNPs in the first intron, and examined the association between c.896 þ 223A4G and obesity as well as related phenotypes. Our study shows no increased risk of obesity for the novel variant and no significant differences in BMI or BMI SDS according to genotype among normal weight adolescents or among children and adolescents with severe FTO variants and insulin action in obese children and adolescents JA Jacobsson et al obesity.…”
Section: Discussionmentioning
confidence: 99%
“…The fat mass and obesity-associated gene (FTO) was recently identified as an obesity candidate gene by three largescale and independent genome-wide association studies, which strongly associated several single nucleotide polymorphisms (SNPs) of FTO with obesity-related traits, including body mass index, hip circumference and body weight. 1 --3 Significant associations between FTO and obesity were independently replicated in many other studies of different populations, including Korean, 4 Japanese, 5 18,20 --22 In mice, FTO deficiency caused postnatal growth retardation and a significant reduction in adipose tissue and lean body mass, 23 and FTO deletion resulted in lesser postnatal growth and lower serum IGF-1 levels. 24 Another mouse model with a missense mutation in FTO maintained linear growth but developed a lean phenotype.…”
Section: Introductionmentioning
confidence: 89%